1981
DOI: 10.1007/bf02926693
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilatation of urethral strictures

Abstract: Postinflammatory and posttraumatic urethral strictures present a significant clinical problem. Conventional dilatation techniques are usually associated with recurrence and aggravation of the strictures. This is attributed to the mucosal and periurethral trauma associated with conventional dilatation methods. The initial results in seven patients undergoing balloon dilatation for urethral strictures are presented. The method is relatively atraumatic and painless, and better long-term results are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…However, despite the utility of BD, there have been few reports of urethral dilation not involving benign prostate hyperplasia . Russinovich et al first reported the usefulness of BD for urethral stricture in 1980 . BD was initially used to dilate stenotic lesions, but has since been shown to be associated with a low risk of mis‐dilation, including when used in case of a normal urethra and the external urinary orifice .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the utility of BD, there have been few reports of urethral dilation not involving benign prostate hyperplasia . Russinovich et al first reported the usefulness of BD for urethral stricture in 1980 . BD was initially used to dilate stenotic lesions, but has since been shown to be associated with a low risk of mis‐dilation, including when used in case of a normal urethra and the external urinary orifice .…”
Section: Discussionmentioning
confidence: 99%
“…However, if the stricture ex tends over the entire urethra, treatment is extremely dif ficult by conventional procedures. Several reports have revealed that concentric dilatation using torpedo-type balloons can be employed for postinflammatory and posttraumatic urethral strictures, and is more precise and less traumatic to the urethra [1,2], However, bal loon dilatation for the entire urethral stricture has been scarcely reported. Recently, balloon dilatation of the prostatic urethra with a large balloon catheter has been applied safely and successfully for benign prostatic hy perplasia [3], We have performed balloon dilatation of the prostatic urethra for patients with urinary retention due to benign prostatic hyperplasia with satisfactory results [4].…”
Section: Discussionmentioning
confidence: 99%
“…The development of the balloon angioplasty catheter has expanded the indications and increased the safety of the technique. More recently this technology has been applied to stenotic lesions in nonvascular tubular structures such as the bile ducts [1 ], gastrointestinal tract [2], urethra [3], and ureter [4-1 1]. Although successful ureteral dilation has been reported [4-1 3], further experience is needed to determine the value of the procedure.…”
Section: Percutaneousmentioning
confidence: 99%